The terminology of inheritance law in Poland and in France: translation difficulties - Pieprzyca, Piotr (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The article deals with the problems of translating certain terms in the field of Polish and French inheritance law. At the beginning, the author presents the general principles of inheritance law in both legal systems. Then he makes a comparative analysis of three pairs of terms that due to legal-linguistic differences in the terminology of Polish and French inheritance law can cause problems in translation. The aim of this paper is to demonstrate that in addition to the necessary linguistic skills, the translator should also have extensive knowledge of law in order to make correct and precise translations.